Evaluation of irrigation and shading methods on nursery production of onion (Allium cepa L.) - Tripathi, PC; Lawande, KE (Vegetable Science, 2011)
Kharif onion (Allium cepa L.), which is 20 % of total onion production, plays crucial role in filling supply gap from October -February. The productivity of kharif onion is very low as compared to other seasons. The kharif onion crop must be ready for harvest in the month of October-November to get higher profit. A study was undertaken at NRC for Onion and Garlic, Rajgurunagar during 2002-2005 with two methods of irrigation and six methods of shading for the production of nursery in summer months. It was found that growing of nursery on drip irrigation under 50% agrishade net or hessian cloth ensures 80-83% of seed germination with 58% final seedling stand as against 49 % and 27% respectively in surface irrigation with no shade.